Assessment of the quality of life of patients with achalasia of the cardia after videoendoscopic Heller cardiomyotomy with Dor fundoplication - E. A. Tseymakh; V. A. Gankov; G. I. Bagdasaryan; A. R. Andreasyan; S. A. Maslikova (Acta Biomedica Scientifica)
Background. The leading symptom of achalasia of cardia (AC) is dysphagia, along with other symptoms significantly affecting the quality of life of patients.The aim. Based on the results of questioning patients using special and general questionnaires and using special methods for studying the closing function of the cardia, to evaluate the quality of life of patients with stages 2–4 of AC after video-laparoscopic esophagocardiomyotomy according to Heller with anterior hemiasophagofundoplication according to Dor.Materials and methods. The basis of the work was the analysis of the results of esophagocardiomyotomy according to Heller with anterior hemiesophagofundoplication according to Dor in 106 patients with stages 2–4 of AC. The postoperative follow-up period averaged 2 ± 0.4 years. In the pre- and postoperative periods, the results of fluoroscopy of the esophagus and stomach, manometry of the esophagus and the esophageal-gastric junction were studied, and three questionnaires were used (Eckhardt scale, GIQLI questionnaire and SF-36).Results. Analysis of the data obtained showed that the clinical manifestations of the disease in the postoperative period decreased in all patients with stages 2–4 of AC, the results in patients with stage 2 were better than in patients with stages 3 and 4 (p < 0.05). The results of fluoroscopy of the esophagus and stomach, manometry of the esophagus and the esophagogastric junction showed improvement in the postoperative period in patients at all stages of the disease, the results of patients with stage 4 were worse compared with stages 2 and 3 (p < 0.05).Conclusion. Videoendoscopic esophagomyotomy according to Heller with anterior fundoplication according to Dor significantly reduces the severity of clinical manifestations of AC and improves the quality of life in patients with stages 2–4 of AC, as a result of which surgery should be recommended to patients already at stage 2 and organ-preserving surgery at stage 4 of the disease.